Incidence and characteristics of invasive fungal diseases in allogeneic hematopoietic stem cell transplant recipients: a retrospective cohort study. Issue 1 (December 2015) - Harrison, Nicole; Mitterbauer, Margit; Tobudic, Selma; Kalhs, Peter; Rabitsch, Werner; Greinix, Hildegard; Burgmann, Heinz; Willinger, Birgit; Presterl, Elisabeth; Forstner, Christina
Abstract Background Allogeneic hematopoietic stem cell transplant (HSCT) recipients experience an increased risk for invasive fungal diseases (IFDs). Methods This retrospective cohort study at the Medical University of Vienna aspired to assess the incidence, characteristics and the outcome of IFDs as well as the associated risk factors in a setting where only 43 % of patients were given systemic antifungal prophylaxis during aplasia. IFDs were classified as probable or proven according to the EORTC/MSG consensus group. All adult patients (n = 242) receiving an allogeneic HSCT at the University Hospital of Vienna from January 2009 to December 2013 were enrolled. Results The primary outcome of this study was the one-year incidence for IFDs after HSCT, which was 10.3 % (25/242). Overall 28 patients experienced an IFD – 20 probable and 8 proven – with invasive aspergillosis being the predominant IFD (n = 18), followed by invasive candidiasis (n = 7) and pneumocystis pneumonia (n = 3). Patients with an IFD were more likely to be admitted to an intensive care unit (64 % versus 12 %, p < 0.0001) and had a significantly higher mortality in the first year after HSCT (48 % versus 25 %, p = 0.02). Multivariate regression analysis revealed that intensified immunosuppressive therapy (high-dose cortisone and basiliximab or etanercept) because of severe graft-versus-host disease (adjusted odds ratio (AOR) 3.6, p = 0.01) and transplant-associated microangiopathy (AOR 3.7, p = 0.04) were associated with an increased risk for IFD, while antifungal prophylaxis given during aplasia and post-engraftment was associated with a decreased risk (AOR 0.3, p = 0.02). Conclusions We documented a one-year incidence for IFDs of 10.3 % and no selection of rare pathogens at a centre with moderate use of antifungal prophylaxis. Intensified immunosuppressive therapy and transplant-associated microangiopathy were significant risk factors for IFDs.